Faktor-Faktor Yang Mempengaruhi Minat Siswa SMA Untuk Melanjutkan Pendidikan Ke Perguruan Tinggi dengan Latent Class Regression Analysis - Sinaga, Melly Nia Fajriani; Dur, Sajaratud; Cipta, Hendra (Universitas Cokroaminoto Palopo, 2024)
Interest is an internal component within an individual that greatly influences his actions. Education is the process of changing the attitudes and behavior of a person or group in an effort to mature a person through teaching or training. The aim of this research is to determine the factors that influence high school students' interest in continuing their education to higher education using the latent class regression analysis method. The latent class regression analysis method can determine the influence of accompanying variables or covariates in the formation of latent classes. The most dominant factors influencing high school students' interest in continuing their education to higher education are needs, facilities and attention. In the first class the influencing factor is need. In the second and third classes the influencing factor is facilities. In the fourth class the influencing factor is attention.